ANALISIS SIKAP PEDULI LINGKUNGAN DI SEKOLAH DASAR - Zakiyah, Sarah; Yulistina Nur DS (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study looked at how elementary school students treat the environment. To preserve the environment in the future, it is very important to instill an attitude of caring for the environment from an early age. The research was conducted through surveys given to teachers and students in several elementary schools. The results of the analysis show that the majority of students have good environmental awareness. However, there are several things that need to be improved, such as increasing understanding of the importance of waste management and recycling. Education about the environment provided at school, the role of teachers, and parental support are some of the factors that influence environmental care attitudes. According to this research, elementary school curricula should include stronger environmental education and more school-family collaboration.